Investigation of the compressive mechanical properties of boron nitride nanotubes - Seah, Terence Capriane (2017)
Since the discovery of carbon nanotubes (CNT), there has been a flourish of research for both the experimental and complimenting theoretical studies of various nanotubes. The excellent properties of CNTs such as their high mechanical strength and semiconductor properties have sparked an interest to find other hollow tubular structures with similar or better properties. One such material has been identified as boron nitrite nanotubes due to their resembling hexagonal configuration (hexagonal boron nitride (h-BN)). In this report, we study the mechanical effects of CNTs produced by thermal chemical vapor deposition (TCVD) and also BNNTs which were produced by using CNT arrays as a template. By putting both the CNT and BNNTs samples though cyclic uniaxial compressions at strains of 30%, 50%, 70% and 90%, we are able to compare the different materials and their differing properties. It is seen that the CNT samples deform plastically under compression with minute reforms. This study provides insight into the mechanical behaviours of CNT arrays.